2018
DOI: 10.4103/ijps.ijps_154_17
|View full text |Cite
|
Sign up to set email alerts
|

Is multiple session of intralesional bleomycin mandatory for complete resolution of macrocystic lymphatic malformation?

Abstract: Background:Intralesional bleomycin scelro-therapy has become a favored line of treatment for macrocystic lymphatic malformations. However the need for multiple sessions is a drawback associated with this treatment modality. Our aim is to document whether multiple session of intra- lesional sclero-therapy is necessary for complete resolution of cystic lymphatic malformation.Method:Intralesional bleomycin under Ultrasound guidance was used for macrocystic lymphangioma at concentration of 3mg/ml but not exceeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Injection of sclerosing agents is more effective in macrocystic lesions [4,13,14]. We had a patient with macrocystic LM in the anterior abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of sclerosing agents is more effective in macrocystic lesions [4,13,14]. We had a patient with macrocystic LM in the anterior abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of our patients come from low socioeconomic status bleomycin is also an economically viable alternative. Report of the intralesional aqueous solution of bleomycin is limited[ 13 14 ] though at our center we are using aqueous bleomycin with promising results. [ 15 ] The mode of action of belomycin in LM is the loss of secretory power caused by drug-induced inflammation on the endothelial lining rather than the killing of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional injection of bleomycin in the treatment of lymphangioma was first used in 1977 by Yura et al [13] Good results of bleomycin injection were reported in patients who had undergone previous surgery with incomplete resection and in patients with postoperative recurrence. Since then, many studies have been reported, and success rates have been reported varying from 35.7% to 91% for 'excellent response' and from 82% to 100% for 'good response' [14][15][16][17] . In the current study, an 'excellent response' to treatment was found in 55% of the cases and a 'good response' in 95% of the cases.…”
Section: Discussionmentioning
confidence: 99%